Do Education and the Labor Market Speak the Same Language? Challenges of the ESCO European Classification of Occupations in Mapping Today’s Professional Translators - Aguayo-Arrabal, Natividad (John Benjamins Publishing, 2023)
This paper addresses the need for terminology convergence and the systematic use of up-to-date descriptors and concepts in the European higher education and labor market environments. Rapid developments in the language industry are remodelling the translation profession in particular and generating new processes, new training needs and, therefore, a new skills demand. Changing market expectations, cross-occupational mobility and multifaceted professional profiles in the translation industry claim to exploit the full potential of standard and multilingual taxonomies like ESCO--the European Classification of Skills, Competences, Qualifications and Occupations. This research draws on the European Master’s in Translation (EMT) competence framework for 2018-2024 to perform a descriptive analysis of the English and Spanish entries for the occupation of “translator” in ESCO’s latest 2020 version. Findings suggest that ESCO’s content could be aligned with the professionally oriented EMT framework to overcome shortcomings in representing translators’ identity and present the reality of the translation market, while matching its content more accurately to the most relevant skills and competences generally developed in current translator training programmes.
https://openpolicyfinder.jisc.ac.uk/id/publication/10894
Keywords: Servicios de traducción; Traductores; Traducción - Estudio y enseñanza superior; ESCO classification; Employability; Translator training; Translator competence; EMT competence framework